The Implementation of Good Corporate Governance on Business Contracts of Companies in Way Kanan Region (A Study of PT Waykanan Makmur) - Bachri, Erlina; Arrahman, Dhifa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Perseroda, as a Regional State-Owned Enterprise, has a specific nature as it conducts business operations for profit-making purposes. However, its assets are derived from separated regional finances, so all corporate legal actions, especially in the preparation and execution of business contracts, must be carried out professionally, transparently, and accountably in accordance with the applicable legal regulations. The research method used in this study is a combination of normative legal and empirical legal approaches. The issues discussed in this research include the implementation of Good Corporate Governance (GCG) principles in the execution of commercial contracts by PT Way Kanan Makmur and the relationship between contract law principles, particularly the principle of pacta sunt servanda. The findings indicate that the implementation of Good Corporate Governance in the execution of business contracts by PT Way Kanan Makmur has not been fully optimized and has not been fully implemented based on the values of transparency, accountability, and caution. As a result, this may lead to legal risks and company deficits. This study concludes that the implementation of contract law principles must align with the practice of Good Corporate Governance to prevent future regulatory challenges.